Microencapsulation of Zn-Al alloy as a new phase change material for middle-high-temperature thermal energy storage applications. (15th October 2020) - Kawaguchi, Takahiro; Sakai, Hiroki; Sheng, Nan; Kurniawan, Ade; Nomura, Takahiro
Highlights: Micro-encapsulated phase change material (MEPCM) for middle-high temperature applications are achieved. The MEPCM is composed of oxide shells and Zn-Al alloy core. The MEPCM exhibits a phase-change temperature of 437–512 °C and latent heat of 117 J g −1 . The MEPCM composites exhibits excellent durability up to100 heating and cooling cycles. Abstract: Thermal energy storage (TES) that utilizes renewable energy and industrial waste heat has recently attracted attention. For the development of TES technology, latent heat storage (LHS) technology using phase change materials (PCMs) is necessary. Covering a PCM with a thermally and chemically stable shell to form a microencapsulated PCM (MEPCM) expands applicability. In this study, for the first time, the authors report the microencapsulation of Zn-30 wt%Al alloy, a new PCM for middle-high temperature (400–500 °C) applications. The microencapsulation process was conducted in two main steps, viz. formation of an AlOOH-based shell on the PCM particles by boehmite treatment and heat-oxidation treatment in an O2 atmosphere to form an oxide shell. Furthermore, composites were synthesized by sintering the MEPCMs with glass frit (GF) as the sintering agent. The prepared MEPCM had multilayers with 500 nm thickness of ZnO and 300 nm thickness of Al-oxide. It exhibited a phase-change temperature of 437–512 °C and latent heat of 117 J g −1 . About 75% of the MEPCM-particles retained their spherical shape after 100 melting and solidification cycles, in addition, the MEPCM-GF composite completely retained their shape and thermal energy storage performances after 100 melting and solidification cycles. Therefore, the authors believe that the MEPCMs and their composites described in this study have the potential to develop new applications involving thermal energy storage, transportation, and management.